2007
DOI: 10.1002/mus.20932
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high‐intensity focused ultrasound on nerve conduction

Abstract: The effects of various exposures (intensity, duration) of high-intensity focused ultrasound (HIFU) on sciatic nerve conduction were investigated in vivo in rats. The objective was to identify HIFU exposures that produce biological effects ranging from partial to complete conduction block, indicating potential use of HIFU as an alternative to current clinical methods of inducing nerve conduction block. In the study, 26 nerves were exposed and treated with 5-s applications of 5.7-MHZ HIFU with acoustic intensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 19 publications
(28 reference statements)
5
67
0
Order By: Relevance
“…An ultrasound-mediated nerve conduction block can be achieved with lower acoustic energy dose, suggesting that the nerve fibers may be highly sensitive to HIFU energy. 10 Therefore, the HIFU may offer benefit to RDN by an efficient and direct heating generation at the target nerves.…”
Section: Discussionmentioning
confidence: 99%
“…An ultrasound-mediated nerve conduction block can be achieved with lower acoustic energy dose, suggesting that the nerve fibers may be highly sensitive to HIFU energy. 10 Therefore, the HIFU may offer benefit to RDN by an efficient and direct heating generation at the target nerves.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support a previous study showing that the CAPs of normal rat sciatic nerves were partly and temporarily blocked at low exposure (390 W cm 22 , 5 s, 5.7 MHz). 8 The degree of suppression of the HIFU-treated diabetic nerves was less than that of the control nerves, and the duration from suppression to recovery was relatively long.…”
Section: Discussionmentioning
confidence: 99%
“…5 6 Furthermore, HIFU has also been applied to suppress nerve conduction and was able to produce a complete and temporary conduction block of bullfrog sciatic nerves in vitro, 7 whilst in rats CMAPs in plantar foot muscles were partly and temporarily blocked by HIFU. 8 However, additional investigations of the effects of HIFU on neuropathic nerves are required. In addition, previous data described the effects on sensory and motor nerves together; thus, the influence of HIFU on sensory nerves alone is uncertain.…”
mentioning
confidence: 99%
“…15,25,26,70,86 Other studies have demonstrated activation of neural tissue, both peripherally and in the CNS. 32,50,81 These effects have been postulated to occur as a result of mechanical stimuli (reversible) and thermal ablation (potentially irreversible).…”
Section: Neuromodulation and Epilepsymentioning
confidence: 99%